(Dis)Embodied Cognition: Phenomenology, Spirit(ual)ism, and Performance in Proust - Paul Aarstad (Studies in 20th & 21st Century Literature, 2019)
A psychical researcher among Marcel Proust’s contemporaries called belief in the paranormal “the Dreyfus case of science.” References to spirit-life abound in Proust’s fiction, but critics have resisted readings that attend seriously to the numerous references in À la recherche du temps perdu to reincarnation, spirit-possession, and, especially, mediumship. The paper reads them through the lens of long-standing critical controversies, particularly concerning the relationship of Proust’s aesthetics and ontology with those of Henri Bergson and Maurice Merleau-Ponty. The paper accepts Nathalie Aubert’s finding in her 2011 essay “Proust et Bergson: La mémoire du corps” that Proust’s insistence on embodiment validates the reluctance of critics since Georges Poulet to connect him with Bergson and makes him, in a sense, a phenomenologist avant la lettre. The paper argues, however, that for Proust a phenomenological interpretation neglects some varieties of experience, and it investigates ways metaphors, particularly in the context of musical performance, drawn from spiritualism inflect his phenomenology and address its limitations.
Keywords: Spiritualism; Spiritism; phenomenology; Proust; Bergson; Merleau-Ponty